X-ray scattering in the elastic regime as source for 3D imaging reconstruction technique. (November 2015) - Kocifaj, Miroslav; Mego, Michal
Abstract: X-ray beams propagate across a target object before they are projected onto a regularly spaced array of detectors to produce a routine X-ray image. A 3D attenuation coefficient distribution is obtained by tomographic reconstruction where scattering is usually regarded as a source of parasitic signals which increase the level of electromagnetic noise that is difficult to eliminate. However, the elastically scattered radiation could be a valuable source of information, because it can provide a 3D topology of electron densities and thus contribute significantly to the optical characterization of the scanned object. The scattering and attenuation data form a complementary base for concurrent retrieval of both electron density and attenuation coefficient distributions. In this paper we developed the 3D reconstruction method that combines both data inputs and produces better image resolution compared to traditional technology. Highlights: Scattered and attenuated signals form complementary base for 3D reconstruction. Generalized theoretical solution is based on bulk scattering along a beam path. 3D map of the electron density can be retrieved by solving an integral equation. S-detector records scattered beams, while D-detector receives direct beams. Rayleigh scattering is taken into consideration.